2019
DOI: 10.1007/s00412-019-00709-5
|View full text |Cite
|
Sign up to set email alerts
|

Srs2 helicase prevents the formation of toxic DNA damage during late prophase I of yeast meiosis

Abstract: Proper repair of double-strand breaks (DSBs) is key to ensure proper chromosome segregation. In this study, we found that the deletion of the SRS2 gene, which encodes a DNA helicase necessary for the control of homologous recombination, induces aberrant chromosome segregation during budding yeast meiosis. This abnormal chromosome segregation in srs2 cells accompanies the formation of a novel DNA damage induced during late meiotic prophase-I. The damage may contain long stretches of single-stranded DNAs (ssDNAs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 95 publications
2
11
0
Order By: Relevance
“…Previous studies had shown that loss of Srs2 activity causes delays and defects in meiotic nuclear division, as well as reduced sporulation and spore viability (Palladino and Klein, 1992;Sasanuma et al, 2013b). Our current study and an accompanying study (Sasanuma et al, 2019) have identified recombination abnormalities in meiosis I prophase that are likely the cause of abnormal nuclear division in srs2 mutants.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Previous studies had shown that loss of Srs2 activity causes delays and defects in meiotic nuclear division, as well as reduced sporulation and spore viability (Palladino and Klein, 1992;Sasanuma et al, 2013b). Our current study and an accompanying study (Sasanuma et al, 2019) have identified recombination abnormalities in meiosis I prophase that are likely the cause of abnormal nuclear division in srs2 mutants.…”
Section: Discussionsupporting
confidence: 64%
“…The observation of persistent Rad51 aggregates in srs2 mutants (Figure 4; Sasanuma et al, 2019) suggests that Srs2 has a similar function during meiosis. Interestingly, while aggregate formation does not require progression through meiosis I (Sasanuma et al, 2019), the absence of aggregates from ndt80∆ mutants, and from NDT80 cells with foci or linear arrays of the SC protein Zip1 (Figs. 5b and 6; Sasanuma et al, 2019), indicates that Rad51 aggregates do not form until cells have exited from pachytene and disassembled SC.…”
Section: Persistent Abnormal Recombination Intermediates In Srs2 Mutantsmentioning
confidence: 84%
See 3 more Smart Citations